Validation of the Mandarin Chinese Version of the Pain Sensitivity Questionnaire. Issue 2 (6th June 2017) - Quan, Xiaoli; Fong, Daniel Yee Tak; Leung, Angela Yee Man; Liao, Qin; Ruscheweyh, Ruth; Chau, Pui Hing
Abstract: Background and Aim: The Pain Sensitivity Questionnaire (PSQ), a self‐reported scale, has been used to assess the pain sensitivity level in a Caucasian population. However, a validated Mandarin Chinese version of the PSQ is not available. This study was aimed to translate the PSQ into Mandarin Chinese (PSQ‐C) and validate it to measure pain sensitivity among Chinese people. Methods: The English version of the PSQ has been translated into Mandarin Chinese (PSQ‐C), according to the standard steps of cross‐cultural adaptation of self‐reported scales. Three of the 17 items were revised owing to cultural adaptation. The final version was validated on a population of 182 Chinese people in Changsha City, China, during October to December 2015. The participants underwent electrical experimental pain testing. The psychometric properties of the PSQ‐C and its subscales were examined. Results: The Cronbach's alpha coefficients for the PSQ‐C‐total, PSQ‐C‐moderate, and PSQ‐C‐minor were 0.90, 0.86, and 0.81, respectively. Acceptable test‐retest reliability, content validity, and construct validity were demonstrated. Concurrent validity was shown via significant positive correlations between PSQ‐C scores and perceived pain intensity at pain threshold and during pain stimulation with a fixed intensity. Convergent validity was shown via significant positive correlations between Pain Catastrophizing Scale scores and PSQ‐C scores. Known group validity was demonstrated via higher PSQ‐C‐total and PSQ‐C‐moderate scores among those with high neuroticism scores. These results indicate that the PSQ‐C has reasonably good psychometric properties, similar to the original English and German versions. Conclusion: The PSQ‐C is a reliable and useful tool to assess pain sensitivity levels in a Chinese population.